2018
DOI: 10.1038/s41598-018-24949-0
|View full text |Cite
|
Sign up to set email alerts
|

MitoQ supplementation prevent long-term impact of maternal smoking on renal development, oxidative stress and mitochondrial density in male mice offspring

Abstract: To investigate the effect of maternal MitoQ treatment on renal disorders caused by maternal cigarette smoke exposure (SE). We have demonstrated that maternal SE during pregnancy increases the risk of developing chronic kidney disease (CKD) in adult offspring. Mitochondrial oxidative damage contributes to the adverse effects of maternal smoking on renal disorders. MitoQ is a mitochondria-targeted antioxidant that has been shown to protect against oxidative damage-related pathologies in many diseases. Female Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Our previous studies in mice have repeatedly shown that MSE can reduce the level of endogenous antioxidant Manganese Superoxide Dismutase in the brain, kidney, and lungs of adult offspring accompanied by increased Reactive Oxygen Species (ROS) levels in those organs; interestingly, antioxidant supplementation during pregnancy could completely or partially reverse the adverse effects on those organs induced by MSE (Chan et al, 2017;Sukjamnong et al, 2017Sukjamnong et al, , 2018. The endogenous antioxidant enzyme system is established in the second and third trimester of pregnancy and continues to develop in early childhood (Fanucchi, 2004).…”
Section: The Role Of Oxidative Stress In the Development Of Asthma Inmentioning
confidence: 99%
“…Our previous studies in mice have repeatedly shown that MSE can reduce the level of endogenous antioxidant Manganese Superoxide Dismutase in the brain, kidney, and lungs of adult offspring accompanied by increased Reactive Oxygen Species (ROS) levels in those organs; interestingly, antioxidant supplementation during pregnancy could completely or partially reverse the adverse effects on those organs induced by MSE (Chan et al, 2017;Sukjamnong et al, 2017Sukjamnong et al, , 2018. The endogenous antioxidant enzyme system is established in the second and third trimester of pregnancy and continues to develop in early childhood (Fanucchi, 2004).…”
Section: The Role Of Oxidative Stress In the Development Of Asthma Inmentioning
confidence: 99%
“…The content of mtDNA was measured by quantifying mRNA expression of the mitochondrial-encoded gene cytochrome c oxidase subunit 1 (COX1; forward primers 5 -ACTATACTACTACTAA-CAGACCG-3 , reverse primers 5 -GGTTC TTTTTTTCCGGAGTA-3 ) against the nuclearencoded gene cyclophilin A (Ppia) (forward primers 5 -ACACGCCATAATGGCACTGG-3 , reverse primers 5 -CAGTCTTGGCAGTGCAGAT-3 ), as we previously published. 14,15 COX1 expression was standardized to Ppia using the Ct method. The average of the sham group was assigned the calibrator against which all other results were expressed as fold changes.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…In this study we investigated neoplastic cells (HeLa and PANC1), human bone marrow derived mesenchymal stem cells (MSC) (isolated as described previously [21,22]) and cryopreserved whole kidney tissue sections obtained from 13 week old Balb/c mice, which were exposed to either air or smoke in utero, as we have previously demonstrated that they express increased levels of ROS [23]. Full details of cell culture and ethics approvals are included in Supplementary Material note 1.…”
Section: Sample Preparation and Ros Stimulationmentioning
confidence: 99%